Fractal characteristics of acoustic emissions from coal under multi-stage true-triaxial compression. (19th June 2018) - Dexing, Li; Enyuan, Wang; Xiangguo, Kong; Xiaoran, Wang; Chong, Zhang; Haishan, Jia; Hao, Wang; Jifa, Qian
Abstract: The fractal characteristics of acoustic emissions (AEs) are widely used for monitoring and warning of coal and rock dynamic disasters such as coal and gas outburst and rock bursts. However, most research has focused on fractal behavior during coal and rock failure under uniaxial and conventional triaxial compression. For this study, we conducted true-triaxial multi-stage loading tests on coal under different stress conditions. Based on the AE count rate data collected from these experiments, we calculated the fractal dimension of every loading step by the Grassberger and Procaccia algorithm using phase space reconstruction theory. The results show that the AE count rate represents the load during the failure well. In the initial loading stage, AEs are very active; in the initial portion of the load maintenance stage, AE counts decrease gradually until they almost cease later in that stage. AE count rates during failure for all loading steps exhibit fractal features and show a generally consistent pattern. The fractal dimension fluctuates in the early loading stages and then begins to decline, reaching a minimum when failure occurs. The critical fluctuation coefficient where the fractal dimension begins to enter the continuous decline stage is about 55.5%–66.5% of the stress level. The relationship between the change of fractal dimension and the 'quiet period' of AE before coal failure is discussed and the proposal that the combination of two monitoring methods can more effectively predict coal and rock dynamic disasters is put forward.